Genome-wide identification, evolution and expression of the CPP gene family in six Theaceae species - Zheng, Wei; Yang, Chunling; Li, Wenyang; Bu, Wanmeng; Bu, Fujun (Frontiers in Plant Science, 2025)
The Cysteine-rich polycomb-like protein (CPP) gene family encodes transcription factors that function as key regulators in various plant processes, including growth, development, and responses to environmental stresses. However, systematic analysis of this gene family in Theaceae plants remains limited. In this study, we comprehensively identified and analyzed the CPP gene family in six Theaceae species, revealing a total of 65 members that were phylogenetically classified into two distinct subfamilies. Multiple sequence alignment revealed that all CPP proteins contain conserved CXC domains (C1 and C2) and an intervening R motif. Gene structure analysis indicated that Class II genes are more conserved, with a predominant structure of 8 exons (71% of members). In contrast, Class I genes most contained 10 exons (48.4%). Codon usage bias analysis identified two distinct groups: 22 codons with high usage frequency and 42 with low usage. Collinearity analysis suggested that whole-genome duplication was the primary driver of the expansion of the CPP gene family, with no tandem duplications detected. A total of 82 types of cis-regulatory elements were identified, with stress-responsive elements being the most abundant. Transcriptome analysis showed that Class I CPP genes, such as CsinCPP2, CcheCPP1, and ColeCPP12, had high expression in leaves, apical buds, and stems. Several Class II CPP genes, such as ColeCPP1, CsinCPP9, ColeCPP2, and CcheCPP8, were significantly upregulated in multiple stress. qRT-PCR expression profiling under drought and salt stress in Camellia oleifera yielded results consistent with the transcriptome data. This study provides a comprehensive and detailed analysis of the CPP gene family in Theaceae, offering valuable insights into the evolutionary dynamics and functional diversification of these genes.